Perceptions and responses to cognitive decline in people with diabetes: A systematic review of qualitative studies - Wang, Meijuan; Guan, Xiangyun; Yan, Jingzheng; Michael, Nyagwaswa; Liu, Xueyan; Tan, Ran; Lv, Xiaoyan; Yan, Fei; Cao, Yingjuan (Frontiers in Public Health, 2023)
Objective We aimed at summarizing the perceptions and responses to cognitive decline, assessing the disease management, identifying deficiencies and proposing new strategies for improvement in people with diabetes (PWDs). Methods A comprehensive search was performed in the following nine databases: PubMed, EMBASE, Web of Science, The Cochrane Library, PsycINFO, CINAHL, WanFang, CNKI, and VIP. The Joanna Briggs Institute (JBI) Critical Appraisal Tool for qualitative research was utilized to evaluate the quality of included studies. Descriptive texts and quotations relating to patient experience were extracted from the included studies and thematically analyzed. Results Eight qualitative studies met the inclusion criteria and 2 overarching themes were identified: (1) self-perception of cognitive decline referred to perceived cognitive symptoms, lack of knowledge and, impaired self-management and coping in multiple methods; (2) reported benefits of cognitive interventions referred to how cognitive interventions improved disease management, attitudes and needs of PWDs. Conclusion PWDs described misconceptions about their cognitive decline and suffered from them during disease management. This study provides a patient-specific reference for cognitive screening and intervention in PWDs, supporting disease management with cognitive decline in clinical practice.